Das Markus-Evangelium im Rahmen antiker Historiographie - Becker, Eve-Marie (Mohr Siebeck, 2006)
The Gospel according to Mark against the Backdrop of Ancient Historiography.
PublicationDate: 20191210
Keywords: Markusevangelium -- antike Literaturgeschichte -- antike Historiographie -- Abkürzungen -- Neues Testament -- Array